Diagnosis and Management of Multiple Sclerosis in Children - NAJAFI, Mohammad Reza; NAJAFI, Mohammad Amin; NASR, Zahra (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Najafi MR, Najafi MA, Nasr Z. Diagnosis and Management of Multiple Sclerosis in Children. Iran J Child Neurol. Summer 2016; 10(3): 13-23. Abstract Growing evidence indicates the safety and well toleration of treatment by Disease-modifying in children suffering multiple sclerosis (MS). The treatment is not straight forward in a great number of patients, thus patients with pediatric MS must be managed by experienced specialized centers. Common treatments of multiple sclerosis for adults are first-line therapies. These therapies (firstline) are safe for children. Failure in treatment that leads to therapy alteration is almost prevalent in pediatric MS. Toleration against current second-line therapies has been shown in multiple sclerosis children. Oral agents have not been assessed in children MS patients. Although clinical trials in children are insufficient, immunomodulating managed children, experience a side effect similar to the adult MS patients. However, further prospective clinical studies, with large sample size and long follow-up are needed to distinguish the benefits and probable side effects of pediatric MS therapies. References Julian L, Serafin D, Charvet L, Ackerson J, Benedict R, Braaten E, et al. Cognitive Impairment Occurs in Children and Adolescents With Multiple Sclerosis Results From a United States Network.J Child Neurol 2013;28(1):102-7. Inaloo S, Haghbin S. Multiple sclerosis in children. Iran J Child Neurol 2013;7(2):1-10. Epub 2014/03/26. Patel Y, Bhise V, Krupp L. Pediatric multiple sclerosis. Ann Indian Acad Neurol 2009;12(4):238. Saadatnia M, Najafi MR, Najafi F, Davoudi V, Keyhanian K, Maghzi AH. CD24 gene allele variation is not associated with oligoclonal IgG bands and IgG index of multiple sclerosis patients. Neuroimmunomodulation 2012;19(3):195-9. Inaloo S, Haghbin S. Multiple Sclerosis in Children. Iran J Child Neurol 2013 Spring; 7(2): 1–10. Jutta Gartner PH. MS disease-modifying therapies in children: ECTRIMS 2010;8:21-4. Kornek B A-EF, Rostasy K, Milos RI. Natalizumab therapy for highly active pediatric multiple sclerosis. JAMA Neurol 2013;Apr;70(4):469-75. Yeh E, Weinstock-Guttman B, Ramanathan M, Ramasamy D, Willis L, Cox J, et al. Magnetic resonance imaging characteristics of children and adults with paediatric-onset multiple sclerosis. Brain 2009;132(12):3392-400. Chabas D, Green AJ, Waubant E. Pediatric multiple sclerosis. NeuroRx 2006;3(2):264-75. McDonald WI, Compston A, Edan G, Goodkin D, Hartung HP, Lublin FD, et al. Recommended diagnostic criteria for multiple sclerosis: guidelines from the International Panel on the diagnosis of multiple sclerosis. Ann Neurol 2001;50(1):121-7. Polman CH, Reingold SC, Banwell B, Clanet M, Cohen JA, Filippi M, et al. Diagnostic criteria for multiple sclerosis: 2010 revisions to the McDonald criteria. Ann Neurol 2011;69(2):292-302. Polman CH, Reingold SC, Edan G, Filippi M, Hartung HP, Kappos L, et al. Diagnostic criteria for multiple sclerosis: 2005 revisions to the “McDonald Criteria”. Ann Neurol 2005;58(6):840-6. Krupp LB, Tardieu M, Amato MP, Banwell B, Chitnis T, Dale RC, et al. International Pediatric Multiple Sclerosis Study Group criteria for pediatric multiple sclerosis and immune-mediated central nervous system demyelinating disorders: revisions to the 2007 definitions. Mult Scler2013 Sep;19(10):1261-7. doi: 10.1177/1352458513484547. Krupp LB, Banwell B, Tenembaum S. Consensus definitions proposed for pediatric multiple sclerosis and related disorders. Neurology 2007;68(16 suppl 2):S7-S12. Amato M, Goretti B, Ghezzi A, Lori S, Zipoli V, Portaccio E, et al. Cognitive and psychosocial features of childhood and juvenile MS. Neurology 2008;70(20):1891-7. Ghezzi A, Amato M, Capobianco M, Gallo P, Marrosu G, Martinelli V, et al. Disease-modifying drugs in childhood-juvenile multiple sclerosis: results of an Italian co-operative study. Mult Scler 2005;11(4):420-4. Mikaeloff Y, Caridade G, Tardieu M, Suissa S. Effectiveness of early beta interferon on the first attack after confirmed multiple sclerosis: a comparative cohort study. Eur J Paediatr Neurol 2008;12(3):205-9. Callen D, Shroff M, Branson H, Lotze T, Li D, Stephens D, et al. MRI in the diagnosis of pediatric multiple sclerosis. Neurology 2009;72(11):961-7. Jacobs LD, Cookfair DL, Rudick RA, Herndon RM, Richert JR, Salazar AM, et al. Intramuscular interferon beta-1a for disease progression in relapsing multiple sclerosis. Ann Neurol 1996;39(3):285-94. Pohl D, Rostasy K, Gärtner J, Hanefeld F. Treatment of early onset multiple sclerosis with subcutaneous interferon beta-1a. Neurology 2005;64(5):888-90. Banwell B, Reder A, Krupp L, Tenembaum S, Eraksoy M, Alexey B, et al. Safety and tolerability of interferon beta-1b in pediatric multiple sclerosis. Neurology 2006;66(4):472-6. Tenembaum SN, Segura MJ. Interferon beta-1a treatment in childhood and juvenile-onset multiple sclerosis. Neurology 2006;67(3):511-3. Pohl D, Waubant E, Banwell B, Chabas D, Chitnis T, Weinstock-Guttman B, et al. Treatment of pediatric multiple sclerosis and variants. Neurology 2007;68(16 suppl 2):S54-S65. Kornek B, Bernert G, Balassy C, Geldner J, Prayer D, Feucht M. Glatiramer acetate treatment in patients with childhood and juvenile onset multiple sclerosis. Neuropediatrics 2003;34(03):120-6. Ghezzi A. Immunomodulatory treatment of early onset multiple sclerosis: results of an Italian Co-operative Study. Neurol Sci 2005;26(4):s183-s6. Tenembaum SN, Banwell B, Pohl D, Krupp LB, Boyko A, Meinel M, et al. Subcutaneous Interferon Beta-1a in Pediatric Multiple Sclerosis A Retrospective Study.J Child Neurol 2013:0883073813488828. Sloka JS, Stefanelli M. The mechanism of action of methylprednisolone in the treatment of multiple sclerosis. Mult Scler (Houndmills, Basingstoke, England) 2005;11(4):425-32. Epub 2005/07/27. Gorman MP, Healy BC, Polgar-Turcsanyi M, Chitnis T. Increased relapse rate in pediatric-onset compared with adult-onset multiple sclerosis. Arch Neurol 2009;66(1):54. Shahar E, Andraus J, Savitzki D, Pilar G, Zelnik N. Outcome of Severe Encephalomyelitis in Children Effect of High-Dose Methylprednisolone and Immunoglobulins. J Child Neurol 2002;17(11):810-4. Spalice A, Properzi E, Faro VL, Acampora B, Iannetti P. Intravenous immunoglobulin and interferon: successful treatment of optic neuritis in pediatric multiple sclerosis. J Child Neurol 2004;19(8):623-6. Koziolek M, Mühlhausen J, Friede T, Ellenberger D, Sigler M, Huppke B, et al. Therapeutic Apheresis in Pediatric Patients with Acute CNS Inflammatory Demyelinating Disease. Blood Purification 2013;36(2):92-7. Najafi F, Ghaffarpour M, Najafi M, Aghamohammadi A, Saadatnia M. Prognostic value of intrathecal IgG synthesis in multiple sclerosis: a study in 54 patients. Tehran University Medical Journal 2008;66(1):1-6. Yeh E KL, Ness J, Chabas D, et al. Breakthrough disease in pediatric MS patients: a pediatric network experience: Annual Meeting of the American Academy of Neurology. Seattle WA: 2009. Yeh EA. Diagnosis and treatment of multiple sclerosis in pediatric and adolescent patients: current status and future therapies. Adolesc Health Med Ther 2010;1:61-71. Borriello G, Prosperini L, Luchetti A, Pozzilli C. Natalizumab treatment in pediatric multiple sclerosis: a case report. Eur J Paediatr Neurol 2009;13(1):67-71. Huppke P, Stark W, Zurcher C, Huppke B, Bruck W, Gartner J. Natalizumab use in pediatric multiple sclerosis. Arch Neurol 2008;65(12):1655. Makhani N, Gorman M, Branson H, Stazzone L, Banwell B, Chitnis T. Cyclophosphamide therapy in pediatric multiple sclerosis. Neurology 2009;72(24):2076-82. Rice GP, Hartung H-P, Calabresi PA. Anti-α4 integrin therapy for multiple sclerosis Mechanisms and rationale. Neurology 2005;64(8):1336-42. Polman CH, O’Connor PW, Havrdova E, Hutchinson M, Kappos L, Miller DH, et al. A randomized, placebo-controlled trial of natalizumab for relapsing multiple sclerosis. N Engl J Med 2006;354(9):899-910. Ghezzi A, Pozzilli C, Grimaldi L, Morra VB, Bortolon F, Capra R, et al. Safety and efficacy of natalizumab in children with multiple sclerosis. Neurology 2010;75(10):912-7. Sousa L, de Sa J, Sa MJ, Cerqueira JJ, Martins-Silva A, En Nombre Del Portugal Experience With Natalizumab Study Group Snapshot EN. The efficacy and safety of natalizumab for the treatment of multiple sclerosis in Portugal.: a retrospective study. Revista de Neurologia 2014;59(9):399-406. Epub 2014/10/25. Estudio retrospectivo de la eficacia y seguridad del natalizumab en el tratamiento de la esclerosis multiple en Portugal. Huppke P, Stark W, Zürcher C, Huppke B, Brück W, Gärtner J. Natalizumab use in pediatric multiple sclerosis. Arch Neurol 2008;65(12):1655-8. Hauser SL, Dawson DM, Lehrich JR, Beal MF, Kevy SV, Propper RD, et al. Intensive immunosuppression in progressive multiple sclerosis. A randomized, three-arm study of high-dose intravenous cyclophosphamide, plasma exchange, and ACTH. N Engl J Med 1983;308(4):173-80. Epub 1983/01/27. Weiner HL, Mackin GA, Orav EJ, Hafler DA, Dawson DM, LaPierre Y, et al. Intermittent cyclophosphamide pulse therapy in progressive multiple sclerosis: final report of the Northeast Cooperative Multiple Sclerosis Treatment Group. Neurology 1993;43(5):910-8. Epub 1993/05/01. Hauser SL, Waubant E, Arnold DL, Vollmer T, Antel J, Fox RJ, et al. B-cell depletion with rituximab in relapsing–remitting multiple sclerosis. N Engl J Med 2008;358(7):676-88. Tzaribachev N, Koetter I, Kuemmerle-Deschner JB, Schedel J. Rituximab for the treatment of refractory pediatric autoimmune diseases: a case series. Cases J 2009;2:6609. Carson KR, Focosi D, Major EO, Petrini M, Richey EA, West DP, et al. Monoclonal antibody-associated progressive multifocal leucoencephalopathy in patients treated with rituximab, natalizumab, and efalizumab: a Review from the Research on Adverse Drug Events and Reports (RADAR) Project. Lancet Oncology 2009;10(8):816-24. Beres SJ, Graves J, Waubant E. Rituximab Use in Pediatric Central Demyelinating Disease. Pediatr Neurol 2014 Jul;51(1):114-8. Wynn D, Kaufman M, Montalban X, Vollmer T, Simon J, Elkins J, et al. Daclizumab in active relapsing multiple sclerosis (CHOICE study): a phase 2, randomised, double-blind, placebo-controlled, add-on trial with interferon beta. Lancet Neurol 2010;9(4):381-90. Bielekova B, Howard T, Packer AN, Richert N, Blevins G, Ohayon J, et al. Effect of anti-CD25 antibody daclizumab in the inhibition of inflammation and stabilization of disease progression in multiple sclerosis. Arch Neurol 2009;66(4):483-9. Rose JW, Watt HE, White AT, Carlson NG. Treatment of multiple sclerosis with an anti–interleukin-2 receptor monoclonal antibody. Ann Neurol 2004;56(6):864-7. Ali E, Healy B, Stazzone L, Brown B, Weiner H, Khoury S. Daclizumab in treatment of multiple sclerosis patients. Mult Scler 2009;15(2):272-4. Gorman MP, Tillema J-M, Ciliax AM, Guttmann CR, Chitnis T. Daclizumab use in patients with pediatric multiple sclerosis. Arch Neurol 2012;69(1):78-81. Gorelik L, Lerner M, Bixler S, Crossman M, Schlain B, Simon K, et al. Anti-JC virus antibodies: implications for PML risk stratification. Ann Neurol 2010;68(3):295-303. Bloomgren G, Richman S, Hotermans C, Subramanyam M, Goelz S, Natarajan A, et al. Risk of natalizumab-associated progressive multifocal leukoencephalopathy. N Engl J Med 2012;366(20):1870-80. Sørensen PS, Bertolotto A, Edan G, Giovannoni G, Gold R, Havrdova E, et al. Risk stratification for progressive multifocal leukoencephalopathy in patients treated with natalizumab. Mult Scler 2012;18(2):143-52. Yildirim-Toruner C, Diamond B. Current and novel therapeutics in the treatment of systemic lupus erythematosus. J Allergy Clin Immunol 2011;127(2):303-12. Zappitelli M, Duffy CM, Bernard C, Gupta IR. Evaluation of activity, chronicity and tubulointerstitial indices for childhood lupus nephritis. Pediatr Nephrol 2008;23(1):83-91. Di Filippo S. Anti-IL-2 receptor antibody vs. polyclonal anti-lymphocyte antibody as induction therapy in Pediatr Transplant. Pediatr Transplant 2005;9(3):373-80. Gallagher M, Quinones K, Cervantes-Castaneda RA, Yilmaz T, Foster CS. Biological response modifier therapy for refractory childhood uveitis. Br J Ophthalmol 2007;91(10):1341-4. Giovannoni G, Comi G, Cook S, Rammohan K, Rieckmann P, Sørensen PS, et al. A placebo-controlled trial of oral cladribine for relapsing multiple sclerosis. N Engl J Med 2010;362(5):416-26. Kappos L, Radue E-W, O’Connor P, Polman C, Hohlfeld R, Calabresi P, et al. A placebo-controlled trial of oral fingolimod in relapsing multiple sclerosis. N Engl J Med 2010;362(5):387-401. Chun J, Hartung H-P. Mechanism of action of oral fingolimod (FTY720) in multiple sclerosis. Clin Neuropharmacoll 2010;33(2):91. Comi G, O’connor P, Montalban X, Antel J, Radue E, Karlsson G, et al. Phase II study of oral fingolimod (FTY720) in multiple sclerosis: 3-year results. Mult Scler 2010;16(2):197-207. Cohen JA, Barkhof F, Comi G, Hartung H-P, Khatri BO, Montalban X, et al. Oral fingolimod or intramuscular interferon for relapsing multiple sclerosis.N Engl J Med 2010;362(5):402-15. Mehling M, Lindberg R, Raulf F, Kuhle J, Hess C, Kappos L, et al. Th17 central memory T cells are reduced by FTY720 in patients with multiple sclerosis. Neurology 2010;75(5):403-10. Edwards JC, Szczepański L, Szechiński J, Filipowicz-Sosnowska A, Emery P, Close DR, et al. Efficacy of B-cell–targeted therapy with rituximab in patients with rheumatoid arthritis. N Engl J Med 2004;350(25):2572-81.